Pengaruh Sakti, Kompetensi SDM, dan Komitmen Organisasi Terhadap Kualitas Laporan Keuangan di Ditjen Paud Dikdasmen - Susilo, Joko; Aritonang, Reikman DP. (CV. Green Publisher Indonesia, 2025)
The realization of quality financial reports can be seen from the fulfillment of the qualitative characteristics of financial reports. Government Regulation of the Republic of Indonesia Number 8 of 2006 concerning Financial Reporting and Performance of Government Agencies mandates state financial managers to present financial information in a timely, informative, transparent and responsible manner through financial reports prepared in accordance with government accounting standards with high-quality financial reports. The purpose of the study was to determine the effect of the implementation of financial indtandi (Sakti), human resource competence, organizational commitment to the quality of financial reports in the Directorate General of Early Childhood Education, Elementary Education and Secondary Education. The research method was carried out with quantitative descriptive, which was carried out by distributing questionnaires to 17 respondents as samples. Data processing was carried out using SPSS Software. The results of the study showed a significant and positive effect on H1, namely the Implementation of the Financial Application System at the Agency Level (SAKTI) has an effect on the Quality of Financial Reports, the hypothesis is accepted; H2, namely Human Resource Competence has an effect on the Quality of Financial Reports, the hypothesis is accepted; H3, namely Organizational Commitment has an effect on the Quality of Financial Reports and the simultaneous effect of the hypothesis is accepted; H4, namely the Implementation of the Institutional Level Financial Application System (SAKTI), Human Resource Competence and Organizational Commitment have a simultaneous effect on the Quality of Financial Reports, the hypothesis is accepted..